Experimental Measurements of Drop Size Distributions in 30 mm Diameter Annular Centrifugal Contactor with 30% TBP-Nitric Acid Biphasic System. (23rd June 2013) - Kumar, Shekhar; Mudali, U. Kamachi
Abstract : For design and development of liquid-liquid extraction systems, it is essential to have an accurate estimation of hydrodynamic and mass transfer characteristics of the employed contactor. In the present study, experimental evaluations consisted primarily of determining the maximum solution throughput that could be processed without cross-phase contamination at a given rotor speed, O/A flow ratio, and organic-aqueous solution pair in a 30 mm bowl diameter centrifugal contactor. In addition, analysis included experimental drop size determinations as well as holdup determination. The experimental drop size distributions are expected to be helpful for modeling work.